Inferring autogenically induced depositional discontinuities from observations on experimental deltaic shoreline trajectories. (16th October 2015) - Mikeš, Daniel; ten Veen, Johan H.; Postma, George; Steel, Ronald
Abstract: Palaeo shoreline is a commonly used proxy for palaeo sea level, but only if deposition is continuous and constant will shoreline trajectory T ( l ) completely capture sea‐level time‐series E ( t ). Artificial deltas were generated in the Eurotank flume facility under stepwise tectonic subsidence, periodic sea‐level fluctuation and two periodic water‐discharge scenarios, one in‐phase and the other out‐of‐phase with sea level. Independent input variables tectonic subsidence Y, sea level E and water discharge Q (controlling sediment supply S ) were varied and dependent output variable shoreline trajectory T was monitored. These experiments confirm that deposition is discontinuous even for continuous sediment supply, and this hinders the inference of sea‐level curve from shoreline trajectory. These results justify the here‐developed methodology for converting shoreline trajectory from the space domain to the time domain, thereby improving the accuracy of the inferred sea‐level curve.